Relationship of Retinol Binding Protein Four Serum Level on Endometrial Hyperplasia and Endometrial Carcinoma: Hubungan Kadar Serum Retinol Binding Protein Empat pada Hiperplasia Endometrium dan Carcinoma Endometrium - Ivan Limy; Eddy Suparman; Hermie M. M. Tendean (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objective : To determine the relationship of elevated serum retinol binding protein 4 with abnormal uterine bleeding Methods : This study was an observational quantitative with cross sectional methods, with all women who had abnormal uterine bleeding caused either by endometrial carcinoma or endometrial hyperplasia at RSUP Prof.DR.RD Kandou, and affiliation hospitals from November 2016 until April 2017. Data were analyzed With SPSS version 2.0 to see the significancy level. Results: Of 26 research subjects, 23 subjects with endomtrial hyperplasia and 3 subjects with endometrial carcinoma. From the total of 26 malignancy and hyperplasia diagnoses, 21 had IMT> 25 and 23 were diagnosed with Endometrial Hyperplasia and 3 Carcinoma Endometrium. 18 subjects had elevated serum RBP4 levels, with 15 people with endometrial hyperplasia and 3 with endometrial carcinoma. With the Fischer Exact test statistic, serum retinol binding protein 4 levels were found in both endometrial hyperplasia and endometrial carcinoma p = 1.00, meaning no significant difference for the occurrence of abnormal uterine bleeding. Conclusion: There was no significant association between serum retinol binding protein 4 between endomterium carcinoma and endometrial hyperplasia. Keywords: abnormal uterine bleeding, endometrial carcinoma, endometrial hyperplasia, serum retinol binding protein 4 Abstrak Tujuan : Mengetahui adanya hubungan peningkatan kadar serum retinol binding protein 4 pada hyperplasia endomterium dengan carcinoma endometrium Metode : Penelitian ini adalah jenis kuantitatif observasional secara potong lintang, dengan semua perempuan yang mengalami perdarahan uterus abnormal yang disebabkan oleh hiperplasia endometrium atau carcinoma endometrium di Bagian Kebidanan dan Kandungan Rumah Sakit Umum Pusat (RSUP) Prof.DR.R.D Kandou, dan RS jejaring mulai November 2016 sampai April 2017.Data dianalisa dengan SPSS versi 2.0 untuk melihat tingkat kemaknaannya. Hasil : Dari 26 subjek penelitian, 23 subjek dengan hyperplasia endomtrium dan 3 subjek dengan carcinoma endometrium. Didapatkan data penelitian dari total keganasan diagnosa dan hiperplasia sejumlah 26 orang, sebanyak 21 orang memiliki IM T>25 dan sebanyak 23 orang didiagnosa dengan Hiperplasia Endometrium dan 3 orang karsinoma Endometrium. Didapatkan sebanyak 18 subyek penelitian mengalami peningkatan kadar serum RBP 4, dengan 15 orang yang mengalami hiperplasia endometrium dan 3 orang dengan karsinoma endometrium. Dengan uji statistik Fischer Exact test, didapatkan kadar serum retinol binding protein 4 baik pada hiperplasia endometrium dengan karsinoma endometrium p=1.00, mengartikan tidak mempunyai perbedaan bermakna untuk terjadinya perdarahan uterus abnormal. Kesimpulan : Tidak terdapat hubungan bermakna kadar serum retinol binding protein 4 antara karsinoma endomterium dengan hiperplasia endometrium. Kata kunci : hiperplasia endometrium , kadar serum retinol binding protein 4, karsinoma endometrium, perdarahan uterus abnormal